Sensitivity analysis of the effect of initial imperfections on the (i) ultimate load and (ii) fatigue behaviour of steel plate girders - Kala, Zdenek; Kala, Jirí; Škaloud, Miroslav; Teplý, Bretislav (Journal of Civil Engineering and Management, 2005)
The study is divided into two parts: (i) in the first one, the plate girder (Fig 1) is considered to be exposed to quasi‐constant loading (ie to loads which are either constant or repeated in a very small number of cycles), while (ii) in the other one, the girder is assumed to be subjected to repeated loading. Then it is understandable that the objective of the first part should be to look into the influence of initial imperfections on the static ultimate load of the girder related to the formation of a plastic failure mechanism in it, while that of the second part was to study the effect of imperfections on the stress state under considerably lesser loads, viz under such as to correspond to the development of fatigue cracks in the girder and, consequently, to its fatigue limit state. In this case the state of stress was measured by bending stresses developing in the crack‐prone areas (Fig 4) of the web “breathing” under the repeated loads, which ‐as demonstrated by the Prague experiments ‐ occur at the toes of the fillet welds connecting the “breathing” web with the girder flanges and stiffeners. In both parts, the results of the theoretical investigation were compared with the conclusions of numerous tests carried out at the Institute of Theoretical and Applied Mechanics in Prague. The correlation was found to be very good; for example, the experimental load‐carrying capacity of the girders tested in Prague was close to the mean value of the corresponding theoretical solutions performed for the same girders. Thereby the analytical model applied in the theoretical investigation can be regarded as verified.The theoretical analysis was based on a non‐linear variant of the finite element method, the girder being modelled by means of shell elements and the ANSYS program being applied. All input imperfections were considered to be random quantities. The statistical distributions were introduced according to both experimentally obtained results and data given in literature. Random realisations of input random quantities were simulated by the LHS (Latin Hypercube Sampling) method. By way of sensitivity analysis it was studied to what extend the variability of initial imperfections was reflected in the variability of stresses in the crack‐prone areas of the girder.The main conclusion can be formulated as follows: While the effect of (and sensitivity to) the initial out‐of‐flatness of the girder web, in the case studied of a plate girder whose web is subjected to predominant shear, on the static load‐carrying capacity is (see the results of the first part of the study) very small (only a few p.c), the same effect on the stress state occurring in the crack‐prone areas of the “breathing” web under service loads can be (see the other part of the study) very important. This is also one of the main explanations of the large scatter of the results of the fatigue tests conducted in Prague.Pradinių trūkumų įtakos plieninių sudėtinių sijų (i) kritinei apkrovai ir (ii) nuovargio būviui jautrumo analizėSantraukaTyrimas yra padalytas į dvi dalis: (i) pirmojoje laikoma, kad sudėtinė sija (1 pav.) yra veikiama pastovaus apkrovimo (t. y. apkrovų, kurios pastovios arba kartotinės, tačiau esant labai mažam ciklų skaičiui), (ii) antrojoje dalyje laikoma, kad sija yra veikiama daugkartinių kartotinių apkrovų. Pirmojoje dalyje nagrinėjama pradinių trūkumų įtaka sijos statinei kritinei apkrovai, kai susidaro jos plastinio irimo mechanizmas, antrojoje dalyje nagrinėjama trūkumų įtaka įtempių būviui, kai veikia daug mažesnės apkrovos, kai susidaro sijos nuovargio plyšiai ir jos nuovargio ribinis būvis. Šiuo atveju įtempiu būvis buvo išmatuotas pagal lenkiamuosius įtempius, atsiradusius dėl kartotinių apkrovų sukelto sienelės “kvėpavimo” plyšių išsivystymo (4 pav.), kurie, kaip parodė Prahoje atlikti bandymai, atsiranda apvadinių siūlių, jungiančių “kvėpuojančią” sienelę su sijos juostomis ir standumo elementais, apačioje. Tyrimų rezultatai buvo palyginti su daugkartinių bandymų, atliktų Prahos teorinės ir taikomosios mechanikos institute, išvadomis. Buvo nustatyta aiški koreliacija: sijų eksperimentinė laikomoji galia buvo artima atitinkamų teorinių sprendinių vidutinėms reikšmėms. Todėl analizinis modelis, naudotas teoriniam tyrimui, gali būti laikomas patikimu.Teorinė analizė buvo pagrįsta netiesiniu baigtinių elementų metodo variantu, kai sija buvo sumodeliuota kevaliniais elementais ir buvo naudojama ANSYS programa. Visi trūkumai buvo vertinti kaip atsitiktiniai dydžiai. Statistiniai pasiskirstymai buvo imti remiantis bandymų rezultatais ir literatūros duomenimis. Įtrauktų atsitiktinių dydžių atsitiktiniai pasiskirstymai buvo modeliuoti LHS (Latin Hypercube Sampling) metodu. Jautrumo analizės būdu buvo nagrinėta, kur išplinta pradinių trūkumų kintamumas, kuris atspindi sijos plyšių išsivystymo plotelių įtempių kintamumą.Svarbiausia išvada: nors sijos sienelės pradinio išsikreivinimo įtaka ir jautrumas tuo atveju, kai buvo nagrinėta sudėtinė sija, kurios sienelė yra veikiama vyraujančios šlyties, statinei laikomajai galiai yra labai maža (žr. tyrimo pirmosios dalies rezultatus) (tik keli procentai), ta pati įtaka įtempių būviui, atsirandančiam “kvėpuojančios” sienelės plyšių išsivystymo ploteliuose, kai veikia eksploatacinės apkrovos, gali būti labai svarbi (žr. antrąją tyrimų dalį). Tai vienas iš pagrindinių atsakymų, kodėl nuovargio bandymų, atliktų Prahoje, rezultatų sklaida buvo didelė.Raktiniai žodžiai: jautrumo analizė, yda, plienas, konstrukcijos, nuovargis, projektavimas, sija.First Published Online: 14 Oct 2010